Tripogon sugathakumariae (Poaceae: Chloridoideae: Tripogoninae): a new species from southern Western Ghats, Kerala, India - Jabeena, Manjakulam Khadhersha; Prabhukumar, Konickal Mambetta; Remya, Sivakumaran; Athira, Subramanian; Hareesh, Vadakkoot Sankaran; Maya, Chandrasekharan Nair; Sunil, Chandrasseril Narayanan (Phytotaxa, 2022)
Tripogon sugathakumariae, a new species from Nelliyampathy hills of southern Western Ghats, Kerala, India, is described and illustrated. It is closely similar to T.bromoides but differs by distinct eciliate membraneous ligule fringed with long hairs at the ends of leaf sheath, shorter length of leaf blade, broad and straw-coloured spikelets, unidentate awned upper glume, lemma 3-lobed and 3-awned without a definite lobe between the median and lateral awns and median awn equal or slightly longer than lemma. Detailed description, distribution and ecology are provided along with a photo plate and illustration.